Employee Engagement Level and Its Key Determinants: a Study in the Context of Nepalese Media Sector - Niraula, Damodar (The Batuk, 2020)
This paper aims to measure the level of employee engagement and to propose employee engagement framework. Following two-step sampling method, a questionnaire survey was conducted among the employees of fifteen media houses. The results of the survey are analyzed with the help of SPSS 18 version. Majority of the employees of Nepalese media houses have been found being engaged to their job. The findings confirm that five HR practices: performance appraisal and recognition; participatory culture; working facility; communication; and job and resources are the determinants of employee engagement. Among those, performance appraisal and recognition, and participatory culture, should be the major focus of human resource managers to make the employees engaged. Additionally, the paper can serve as a reference and an analytical tool to researchers for expanding knowledge on the topic.